EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD): A STEP TOWARDS A GENERATION THAT CARES FOR THE ENVIRONMENT - Ihsan Zikri Ulfiandi; Faqihul Hikam Mohammad; Iffah Maulana Putri Hanum Soumena (International Journal of Teaching and Learning, 2026)
This research aims to analyze the implementation of Education for Sustainable Development (ESD) in MTs NU in creating a generation that cares for the environment, in accordance with the vision of MTs NU which is Islamic, Professional, Superior, Trusted, and Environmentally Insightful. A descriptive qualitative approach is used by collecting data through interviews, observations, and documentation. The results of the study show that MTs NU has successfully integrated sustainability values in the curriculum and environmental programs, such as Zero Waste, waste management, composting, nurseries and eco-brick making. These programs significantly increase students' environmental awareness as well as their active involvement in maintaining cleanliness and practicing sustainability. These findings affirm the importance of synergy between Islamic education and environmental sustainability in producing a morally, socially, and environmentally responsible generation. The results of this study can be a model for other educational institutions that want to implement ESD effectively.